Evaluation of the health status of the flora species of the Caucasia Hydrobotanical Garden - Velasquez Velez, Maria Isabel
Plants are a very valuable natural asset for a territory and its communities, reflecting their importance in population centers, as carbon dioxide sinks, refuge for wildlife species, mitigation of local temperature, as well as cultural and other services. . related to urban sustainability; The role of trees can be affected by their state of conservation, limiting their ecosystem services. Currently, the Caucasia hydrobotanical garden, with an area of ​​approximately 7 hectares, has a high biodiversity richness in flora, both in number of species and families and it is observed that some of the individuals do not have the ideal sanitary conditions for their functioning, so the objective of evaluating the conservation status of the flora species in 4 transects is raised, taking into account the dasometric characteristics of DAP and height, as well as qualitative characteristics of individuals such as (Healthy, acceptably healthy, sick), to indicate the health status taking into account the Murillo (1997) method. Several individuals were found with an acceptably healthy health status, which becomes an opportunity to develop different intervention alternatives that promote the care and conservation of the trees in the botanical garden, giving relevance as a strategic urban ecosystem necessary for the fulfillment of SDG 11. Ensure that cities and human settlements are inclusive, safe, resilient and sustainable, from which the municipality's community can benefit.